The Implementation of Program Indonesia Pintar (PIP): A Budget Performance Analysis and Its Impact on Education Access - Heri Susanto; Alvian Alvin Mubarok (AIBPM Publisher, 2025)
The Merdeka Belajar (Freedom to Learn) policy acts as a fundamental pillar in improving access to and the quality of education in Indonesia. Within the Merdeka Belajar Kampus Merdeka (MBKM) framework, the Program Indonesia Pintar (PIP) was introduced as a key initiative to provide financial educational support to children from economically disadvantaged families. To ensure that the PIP's pro-poor budgeting approach effectively benefits its recipients, its implementation must be optimized. This requires a thorough evaluation of budget allocation methods, the distribution process for assistance cards, and the program's overall monitoring and evaluation mechanisms. Such an assessment seeks to measure the effectiveness of the PIP’s budgeting strategy, identify existing challenges, and recommend improvements to enhance the program's efficiency and impact on its beneficiaries. Collaboration among stakeholders is crucial to improving the execution of the PIP’s pro-poor budgeting approach. By strengthening these efforts, the PIP can significantly contribute to the government’s mission under the MBKM framework—promoting quality education and ensuring equitable educational opportunities for all citizens.